Greenhouse gases utilization via catalytic reforming with Sc promoted Ni/SBA-15. (15th December 2022) - Al-Fatesh, Ahmed S.; Kasim, Samsudeen O.; Ibrahim, Ahmed A.; Osman, Ahmed I.; Abasaeed, Ahmed E.; Atia, Hanan; Armbruster, Udo; Frusteri, Leone; bin Jumah, Abdulrahman; Mohammed Alanazi, Yousef; Fakeeha, Anis H.
Graphical abstract: Highlights: Ni and Sc (0.5, 1 and 3 wt.%) were impregnated on mesoporous silica SBA-15 support. Loading Sc and Ni slightly deformed the SBA-15 hexagonal structure. The active Ni interacts with the SBA-15 support and Sc promoter. An optimum loading of 0.5 wt.% Sc gave the highest activity and stability. The studied catalyst of the process generated an H2 /CO ratio of 0.99. Sc loading exceeding 0.5 wt.% decreased the activity. Abstract: This study investigated the performance of supported Ni catalysts in the utilization of greenhouse gases like CO2 and CH4 via dry reforming. The support SBA-15 was impregnated first with Sc at different loadings (0.5, 1, and 3 wt.%) and then with Ni (5 wt.%). The catalysts were first tested up to 8 h on stream with stoichiometric feed as well as methane in excess. The as-prepared catalysts were characterized using BET, XRD, TPR, CO2 -TPD, XPS, TGA, and TEM. This is in accordance with the surface area measurement, XRD, and TEM data. The Ni added to Sc-SBA-15 appeared to interact with both the support and Sc as the intensity and reduction temperature of the Sc promoted catalysts increased relatively to the unpromoted sample depending on Sc content. The catalyst with 0.5 wt.% Sc loading led to the highest conversion and the lowest relative activity loss. The CH4 and CO2 conversions, on average, were 78 and 86 %, respectively, at the end of the runs at 750 °C. The final H2 /CO ratio was 0.99, which is a good value compared to many literature catalysts. This catalyst also showed relatively constant CH4 and CO2 conversions over 80 h on stream. Increasing the Sc loading above 0.5 wt.% was not beneficial in terms of activity.